1980
DOI: 10.3382/ps.0590077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restricted Feeding from 6 to 20 Weeks of Age on Reproductive Performance of Turkeys

Abstract: A study was undertaken to determine the influence of nutrient restriction between 6 weeks and 20 weeks of age on the reproductive performance of commercial turkey breeders. Females were restricted in feed intake to 70% or 60% of full-fed control hens. Males were restricted to approximately 50% of normal feed intake for the same period. The body weight of restrictedfed females was significantly less than that of control hens at 20, 32, and 52 weeks of age. The restricted hens consumed approximately 10% less fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Hocking et al (1987) observed comparable results in broiler breeders fed ad libitum and showed that the higher egg production of broiler breeders limited in point of lay body weight by food restriction is associated with a lower incidence of multiple ovulation. Food restriction experiments in turkeys have not produced consistent increases in egg production, but this procedure has not usually been applied to birds photostimulated before 30 weeks, nor have the treatments tested produced large depressions in body weight at sexual maturity (Balloun, 1974;Jones et al, 1976;Owings and Sell, 1980). Nestor et al (1970; and Bacon et al (1972) have shown that selection for increased growth in turkeys resulted in a greater incidence of yellow follicles developing as pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Hocking et al (1987) observed comparable results in broiler breeders fed ad libitum and showed that the higher egg production of broiler breeders limited in point of lay body weight by food restriction is associated with a lower incidence of multiple ovulation. Food restriction experiments in turkeys have not produced consistent increases in egg production, but this procedure has not usually been applied to birds photostimulated before 30 weeks, nor have the treatments tested produced large depressions in body weight at sexual maturity (Balloun, 1974;Jones et al, 1976;Owings and Sell, 1980). Nestor et al (1970; and Bacon et al (1972) have shown that selection for increased growth in turkeys resulted in a greater incidence of yellow follicles developing as pairs.…”
Section: Discussionmentioning
confidence: 99%
“…During the first egg production season, turkey hens fed ad libitum during the growth, holding, and reproductive phases have been reported to either lose (Borron et al, 1974;Cherms et al, 1976;Thomason et al, 1976;McCartney et al, 1977;Krueger et al, 1978;Potter et al, 1978;Menge et al, 1979;Owings and Sell, 1980;Rosebrough et al, 1980) or gain body weight (Balloun, 1974;Borron et al, 1974;Woodard et al, 1974;Andrews and Morrow, 1978;Meyer et al, 1980;Rosebrough et al, 1980;Nestor et al, 1981) during the reproductive period. Following a forced molting, a gain (Ferguson et al, 1975) or loss in body weight (Thomason et al, 1976) has been reported during the second production period.…”
Section: Introductionmentioning
confidence: 99%
“…Switching from low to high environmental temperatures was associated with body weight loss, while switching from high to low environmental temperature was associated with weight gains during egg production (Thomason et al, 1976;Woodard et al, 1974). Flocks housed in conventional floor pens which initiate egg production in cool weather and continue egg production into hot weather (seasonal flocks) normally lose weight during the reproductive period (Cherms et al, 1976;McCartney et al, 1977;Potter et al, 1978;Owings and Sell, 1980). Conversely, flocks housed in conventional floor pens which initiate egg production in warm or hot weather and continue egg production into cool weather (out of season flocks) gain weight during the reproductive period (Meyer et al, 1980) or maintain relatively constant weight (Krueger et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results for egg production were more variable. Jones et al (1976), Andrews and Morrow (1978), and Voitle and Harms (1978) showed that restricted-fed hens produced significantly fewer eggs, whereas Potter et al (1978), Owings and Sell (1980), Nestor et al (1981), and Ferket and Moran (1986) showed no effect of feed restriction on total egg production.…”
Section: Introductionmentioning
confidence: 90%